Insulin tolerance test predicts the effectiveness of insulin sensitizers in japanese type 2 diabetic patients - Kozawa, Junji (Springer Healthcare Communications, 2011)
INTRODUCTION: The purpose of this study was to assess the efficacy of the insulin tolerance test (ITT) in predicting the effectiveness of insulin sensitizers in type 2 diabetic patients. METHODS: We retrospectively reviewed 360 consecutive patients with type 2 diabetes admitted to Osaka University Hospital, Japan. In 163 of these hospitalized patients, insulin resistance was evaluated by the ITT after their blood glucose level was ameliorated. We then analyzed the association between their clinical characteristics and their glycemic control 6 months after discharge. RESULTS: The rate constant for plasma glucose disappearance, K (ITT), was negatively correlated with body mass index (BMI), waist circumference (WC), and visceral fat area (VFA). The median value of K (ITT) was 1.56 (%/min). In the K (ITT) > 1.56 group (n=81), hemoglobin A(1c) (HbA(1c)) significantly increased in both patients treated with insulin sensitizers (n=10) and patients not treated with insulin sensitizers (n=71). In the K (ITT) ≤1.56 group (n=82), HbA(1c) significantly increased in patients not treated with insulin sensitizers (n=60); however, it was maintained well in the patients treated with insulin sensitizers (n=22). When the patients were divided and analyzed according to the median values of BMI, WC, or VFA, the glycemic control change was not different between the two groups with insulin sensitizers for each parameter. CONCLUSION: Insulin sensitizers were effective in type 2 diabetic patients with high insulin resistance estimated by the ITT. The ITT could be useful to predict the effectiveness of insulin sensitizers.